From bark to hartwood: gender issues in sustainable forest management - Colfer, C.J.P.; Wadley, R.L.; Woelfel, J.; Harwell, E. (1997)
The studies discussed here were designed to assess previously identified human components of sustainable forest management (SFM). These human components include security of intergenerational access to resources, co-management of forests, and the definition of appropriate stakeholders. A variety of methods is currently being tested for cost effectiveness and reliability, in the hopes that people’s well being and their roles in forest management can be routinely assessed. Some of the methods we have used in assessing the human components of SFM include a participatory card sorting technique, “Galileo” cognitive mapping, a local history form, an “Iterative Continuum Method” (ICM), and participatory mapping. These methods are briefly evaluated against the authors’ more qualitative understanding of gender issues in the research context, based on long term, ethnographic fieldwork. This paper reports our attempts and our shortcomings in integrating a gender perspective into the assessment process.